ASSISTÊNCIA DE ENFERMAGEM A PACIENTE COM DIAGNÓSTICO DE SÍNDROME DE STEVENS-JOHNSON- RELATO DE EXPERIÊNCIA - Barasuol, Monica E. C.; Freire, Maria R. A.; Klein, Rúbia N.; Lauter, Dagmar S.; Dallabrida, Francieli A.; Kolankiewicz, Adriane C. B. (Salão do Conhecimento, 2013)
Resumo